2018
DOI: 10.1007/s12105-018-0940-4
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-Related Disease of the Thyroid Gland Requiring Emergent Total Thyroidectomy: A Case Report

Abstract: IgG4-related disease of the thyroid gland is a recently recognized subtype of thyroiditis, often with rapid progression requiring surgical treatment. It is considered as a spectrum of disease varying from early IgG4-related Hashimoto's thyroiditis (HT) pattern to late fibrosing HT or Riedel's thyroiditis patterns. Here, we report a 47-year-old Malay woman presenting with progressively painless neck swelling over 3 years and subclinical hypothyroidism. Computed tomography (CT) scan revealed diffuse thyroid enla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Our patient’s symptoms due to mass effect (dysphagia, airway obstruction) rather than chemical insult (eg, heat or cold intolerance, tremors, changes in energy level, etc.) align with reports of Luiz et al,14 Kang et al,16 and Zhao et al18 in which neck swelling without symptoms of thyroid dysfunction were observed. Indeed, Li et al1 found 39% (11/28) of IgG4-RHT cases to be associated with subclinical hypothyroidism.…”
Section: Discussionsupporting
confidence: 92%
“…Our patient’s symptoms due to mass effect (dysphagia, airway obstruction) rather than chemical insult (eg, heat or cold intolerance, tremors, changes in energy level, etc.) align with reports of Luiz et al,14 Kang et al,16 and Zhao et al18 in which neck swelling without symptoms of thyroid dysfunction were observed. Indeed, Li et al1 found 39% (11/28) of IgG4-RHT cases to be associated with subclinical hypothyroidism.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, in endocrine practice, fine needle aspiration is the first choice in different lesions at the thyroid after initial clinical and ultrasound detection regardless of the underlying pathological report [ 58 , 59 ]. Yet, in RT the procedure is not useful for diagnosis as pointed out by our sample-based analysis (which in some cases was not feasible at all due to “iron-hard” thyroid consistency) [ 45 , 46 , 49 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some suggested that identifying a high level of serum IgG4 in one patient with Hashimoto’s thyroiditis represents an early predictor for developing its fibrotic variant [ 90 ]. Both, RT and the fibrotic variant of Hashimoto’s thyroiditis have been suggested to represent the end stage of a long progressive evolution, but typically a higher risk of non-thyroid IgG4-mediated fibrosis is reported in RT (as opposed to the other entity) [ 58 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with subclinical hypothyroidism, which indicates that the disease course may progress more rapidly. IgG4 HT presents as goitre, and sometimes the thyroid enlarges rapidly, leading to compressive symptoms, which consequently results in a high rate of thyroidectomies as compared with non-IgG4 HT ( 5 , 6 , 19 ). They are more vulnerable to papillary thyroid carcinoma and may have worse clinical outcomes, including a larger tumour diameter and a higher percentage of lymph node metastasis ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Li et al ( 2 ) first proposed dividing HT into IgG4 and non-IgG4 HT based on IgG4 and IgG immunohistochemical staining results in thyroid tissue and found that IgG4 HT had unique clinical, serological, sonographic, and histopathological features compared to non-IgG4 HT ( 3 , 4 ). IgG4 HT can present as goitre, and sometimes the thyroid would become enlarged rapidly, leading to compressive symptoms, possibly requiring surgical removal ( 5 , 6 ). With regard to thyroid function, IgG4 HT is associated with hypothyroidism ( 3 ).…”
Section: Introductionmentioning
confidence: 99%